The Transformation of Scientific Political Philosophy into a Speculative Philosophy of History - Jokubaitis, Linas (Problemos, 2020)
The paper presents an analysis of the three stages of the development of political philosophy since the 17th century. The rise of modern political theory was marked by attempts to develop a philosophy along the lines of natural sciences. These attempts lead to the development of highly speculative and abstract doctrines; political philosophy ceased being a practical discipline. The paper argues that an important aspect of the traditionalist political thought of the 18th century was an attempt to reestablish the link between theory and practice. In the 19th century, the interest in history was supplemented with new premises about the historical process. Political philosophy, which strived to become scientific, became highly dependent on the premises of various philosophies of history.